Prostaglandin E1 Is an Efficient Molecular Tool for Forest Leech Blood Sucking - Zheng, Fenshuang; Zhang, Min; Yang, Xingwei; Wu, Feilong; Wang, Gan; Feng, Xingxing; Ombati, Rose; Zuo, Ruiling; Yang, Canju; Liu, Jun; Lai, Ren; Luo, Xiaodong; et al. (Frontiers in Veterinary Science, 2021)
From a survival perspective, it is hypothesized that leech saliva exhibits certain physiological effects to ensure fast blood-feeding, including analgesia, anesthesia, and anti-inflammation to stay undetected by the host and vasodilatation and anti-hemostasis to ensure a steady, rapid, and sustained blood flow to the feeding site. Many anti-hemostatic compounds have been identified in leech saliva, such as hirudin, calin and bdellin A. However, no specific substance with direct vasodilatory and anti-inflammatory function has been reported from forest leech saliva. Herein, using activity-guided analysis, prostaglandin E1 (PGE1) was identified for the first time as an efficient molecular tool for forest leech blood sucking. The structure of PGE1 was analyzed by nuclear magnetic resonance spectroscopy and high-resolution electrospray ionization mass spectroscopy. PGE1 was found to be primarily distributed in the leech salivary gland (1 228.36 ng/g body weight). We also analyzed how forest leech PGE1 affects platelet aggregation, skin vascular permeability, bleeding time, and pain. Results indicated that PGE1 efficiently inhibited platelet aggregation induced by adenosine diphosphate (ADP) (5 μM) with an IC50 of 21.81 ± 2.24 nM. At doses of 10 nM, 100 nM, and 1 µM, PGE1 increased vascular permeability by 1.18, 5.8, and 9.2 times. It also prolonged bleeding time in a concentration-independent manner. In the formalin-induced mouse paw pain model, PGE1 suppressed acute pain. To the best of our knowledge, this is the first report on PGE1 in invertebrates. The functions of PGE1, such as vasodilation, platelet aggregation inhibition, anti-inflammation, and pain alleviation, may facilitate the ingestion of host blood by leeches.